Riesgo ergonómico en el proceso de transformación de ladrillo tolete en la ladrillera “Las Malvinas” en el municipio de Sogamoso - Patarroyo Martínez, José Felipe; Pedraza López, Kevin Rolando (Universidad Antonio Nariño, 2023)
Through this research, of mixed type and associated with the line of Integrated Management Systems, an Ergonomic Risk analysis is made in the transformation process of Tolete brick in the brick factory "Las Malvinas" located in the municipality of Sogamoso. This is based on the diagnosis of the conditions present in the development of the activities, the identification of all the elements of production and the collection of information through the application of an instrument (survey), which allowed an initial approximation to the current working conditions. This made it easier to identify the biomechanical risks to which workers are exposed and then, once the most relevant methodologies have been selected, to make their quantitative analysis and assessment based on them, in order to prioritize the intervention. Finally, intervention measures are proposed on different fronts, considering those likely to be implemented by the organization, in accordance with the need for intervention and the availability of resources, seeking to minimize the impact on workers.